Analisis Perlindungan Hukum bagi Kurir dalam Kasus COD Melalui Transaksi E-Comerce - Sari, Natalia Desta (Proceedings Series on Social Sciences & Humanities, 2024)
In the era of technological development and online business, electronic buying and selling transactions are increasingly common. E-commerce refers to all buying and selling activities carried out through marketplace media. Marketplace itself is an e-commerce model that acts as an intermediary between sellers and buyers. Sellers who transact on the marketplace only need to buy. All other activities, such as website management will be handled by the platform. Examples of platforms such as Shopee and Lazada are two examples of markets.The purpose of this writing is to provide information to readers about legal protection for couriers. This research uses normative juridical methods. The normative juridical method is a legal research method that uses library materials, literature studies or secondary data sources as reference material for research. The library materials that the author uses in this research are statutory regulations. Based on this method, the research was carried out using a statutory approach and a conceptual approach. The approach to legislation (statute approach) is carried out by reviewing all laws and regulations related to the legal issue being discussed (researched). The conceptual approach departs from the views and doctrines that have developed in legal science.